FORMS AND FUNCTIONS OF OPERATORS FOUND IN TWILIGHT NOVEL - Herman Paseru; I Wayan Ana; Dewa Ayu Kadek Claria (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
This research tries to analyze and discuss about the forms and functions of the operator in English found in the novel entitled Twilight written by Stephanie Meyer as the data source. The method used in conducting this research includes; chose the data source, data collection and data analysis. All the data from the novels are collected through library research by selecting the sentences which are related to the topic and analyzed systematically based on its types and functions. The theories applied to support this paper are the theory of Quirk, et al in their book entitled A Grammar of Contemporary English (1972) as the main theory, the theory of Cobuild in his book entitled English Grammar (1990) and others that are relevant to the topic are used as supporting theories. Based on the result of the analysis, it is found that the operators have four major forms namely do, be, have, and central modals. Besides, the functions of the operators are helping the positive declarative sentence in forming negative, interrogative, and nonassertive. In forming negative, the operator is immediately added with the negator not or the enclitic contracted form n’t and it is placed between the subject and the predication. Then, there are two forms of interrogatives or questions, namely yes-no questions and wh-questions. In yes-no questions, operatoris placed in front of the subject generally and in the wh-questions, the operator follows the wh-words. Besides, the operators also have important function in forming the nonassertive because the nonassertive form usually appears in the negative and interrogative sentences.